2011
DOI: 10.1345/aph.1p764
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of the Safety of Regular Preventive Asthma Medications During Pregnancy

Abstract: Some negative outcomes of preventive asthma medications have been reported, although their direct link with medication use is inconclusive. Selection of preventive medications for asthma management during pregnancy should be based on an assessment of the risks and benefits of medication use versus the risks of poorly controlled asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0
10

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(56 citation statements)
references
References 50 publications
0
46
0
10
Order By: Relevance
“…The National Heart, Lung, and Blood Institute and the Global Initiative for Asthma (GINA) guidelines indicate that pregnant women should maintain their current regiment of asthma medications, including inhaled corticosteroids, long-acting beta agonist, leukotriene modifiers, theophylline, and oral corticosteroids (36, 37). Maintaining asthma control during pregnancy is important as severe asthma, poorly controlled asthma, and asthma exacerbations during pregnancy are associated with increased risk for development of pre-eclampsia and gestational diabetes in the mother and pre-term birth, low birth weight, and perinatal mortality for the baby (36, 38, 39). Future longitudinal studies are needed to track women with asthma prior to pregnancy and throughout the pregnancy to determine if any biomarker or clinical lung function test can be used to predict if asthma symptoms will change during pregnancy.…”
Section: Pregnancy and Asthmamentioning
confidence: 99%
“…The National Heart, Lung, and Blood Institute and the Global Initiative for Asthma (GINA) guidelines indicate that pregnant women should maintain their current regiment of asthma medications, including inhaled corticosteroids, long-acting beta agonist, leukotriene modifiers, theophylline, and oral corticosteroids (36, 37). Maintaining asthma control during pregnancy is important as severe asthma, poorly controlled asthma, and asthma exacerbations during pregnancy are associated with increased risk for development of pre-eclampsia and gestational diabetes in the mother and pre-term birth, low birth weight, and perinatal mortality for the baby (36, 38, 39). Future longitudinal studies are needed to track women with asthma prior to pregnancy and throughout the pregnancy to determine if any biomarker or clinical lung function test can be used to predict if asthma symptoms will change during pregnancy.…”
Section: Pregnancy and Asthmamentioning
confidence: 99%
“…ICSs prevent asthma exacerbations during pregnancy [124] and cessation of ICS during pregnancy is a risk factor for exacerbations (evidence A) [122]. In addition, the use of ICSs as well as β 2 -agonists or montelukast does not increase the risk for fetal abnormalities [125]. Acute exacerbations occurring during pregnancy should be treated aggressively with SABA, oxygen and systemic corticosteroids in order to avoid fetal hypoxia.…”
Section: Pregnancymentioning
confidence: 99%
“…Several studies including a meta-analysis on inhaled corticosteroids have not found an increased risk for congenital malformations (Greenberger and Patterson 1983;Rahimi et al 2006;Källén and Otterblad 2007;Choi et al 2007;Lim et al 2011). No adverse fetal outcomes such as pregnancy-induced hypertension, preterm delivery or low birth weight were documented (Rahimi et al 2006;Lim et al 2011).…”
Section: Corticosteroids (Inhaled)mentioning
confidence: 99%